Exercise-induced pulmonary hypertension assessed by echocardiography in patients with chronic thromboembolic pulmonary disease. (3rd October 2022) - Dhayyat, A; Mykland Hilde, J; Jervan, O; Stavem, K; Ghanima, W; Melsom, M N; Steine, K
Abstract: Background: Many patients with chronic thromboembolic pulmonary disease (CTEPD) without pulmonary hypertension (PH) at rest suffer from exercise intolerance. Exercise echocardiography, which is a noninvasive examination, may have potential to discover exercise-induced PH in these patients, however, its role is scarcely explored in this population. Purpose: To determine the occurrence of abnormal pulmonary pressure during rest and by exercise echocardiography in patients with CTEPD. Methods: In total, 24 patients with CTEPD, all diagnosed after pulmonary embolism, underwent exercise echocardiography with dynamic supine leg exercise using a cycle ergometer. In addition, all participants underwent a modified incremental shuttle walk test (mISWT), pulmonary function tests and measurement of NT pro-BNP. Systolic pulmonary arterial pressure (sPAP) >50 mmHg by echocardiography during exercise was chosen as cutoff to define exercise-induced pulmonary hypertension (EIPH). Left ventricular diastolic dysfunction during stress was defined according to the American Society of Cardiology guidelines from 2016. Mean pulmonary artery pressure was estimated by sPAP measurements using the Chemla formula (0.61 x sPAP + 2 mmHg), and pulmonary vascular resistance (PVR) by the Doppler method (5.19 x TRV 2 /TVI RVOT − 0.4) proposed by Abbas et al. [1]. Subjects with heart failure with reduced or preserved ejection fraction, significant valvular heart disease, chronic pulmonary disease and chronic thromboembolic pulmonary hypertension were excluded. Results: 11 (46%) of the patients had EIPH at peak exercise (range 50 to 89 mmHg). PVR at peak exercise ranged from 2.6 to 5.9 WU, whereas 10 had PVR >3.0 WU. None had unmasked left ventricular diastolic dysfunction during exercise, resting tricuspid regurgitation peak velocity (TR V max) >3.4m/s, or a high probability of PH at rest. Three patients had TR V max between 2.9 and 3.4m/s or intermediate probability of PH. All patients had normal biventricular systolic function at rest and during exercise (Table 2). Conclusion: Patients with CTEPD had normal pulmonary pressures at rest. However, approximately half of the patients showed abnormal rise in pulmonary pressure during exercise, which may explain or contribute to the exercise intolerance in these patients. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Ostfold Hospital Trust